MOF glass fiber composite material and preparation method and application thereof
By compounding MOF materials with glass fiber and functional modification, the stability of MOF materials in high humidity and high temperature conditions is solved, and CO2 capture efficiency and mechanical performance are improved, and it is suitable for industrialization applications.
Patent Information
- Application Number
- CN202411633279.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing MOF materials are prone to degradation under high humidity and high temperature conditions, have reduced adsorption performance, and are high in preparation costs and complex in processes, which limits their industrial application in the field of carbon capture.
By compounding MOF materials with glass fiber, the functional modification layer is used to enhance the performance of the material, including the modification of groups such as amino, carboxyl, and hydroxyl groups to form a stable MOF glass fiber composite material.
It improves the CO2 capture efficiency, enhances the mechanical strength and thermal stability of the material, reduces energy consumption and cost, and is suitable for carbon dioxide capture in industrial environments.
Abstract
Description
Technical Field
[0001] The invention relates to a MOF glass fiber composite material and a preparation method and application thereof, belonging to the technical field of environmentally friendly materials. Background Art
[0002] As global climate change intensifies, carbon dioxide, as the main greenhouse gas, has become a global focus of attention. Existing carbon dioxide capture technologies include chemical adsorption, physical adsorption and membrane separation, but they generally have problems such as high energy consumption, low capture efficiency or poor material stability. Therefore, it is of great significance to develop carbon dioxide capture materials with high adsorption capacity, low cost and high stability.
[0003] Metal-organic framework (MOF) materials have shown great potential in the field of CO2 capture in recent years due to their structural tunability, high specific surface area and good gas adsorption capacity. However, MOF materials have poor mechanical properties and are difficult to be directly applied in the industrial field. Glass fiber, as a material with high temperature resistance, corrosion resistance and mechanical strength, can be combined with MOF to form a stable composite material for large-scale gas capture applications. Therefore, the development of functionalized MOF glass fiber composites has important practical application value.
[0004] In the field of carbon capture, metal organic framework (MOF) materials have become an important research object for gas adsorption, especially carbon dioxide (CO2) capture, due to their high specific surface area, adjustable pore size and designability of chemical properties. In the prior art, MOF materials have shown good CO2 selective adsorption performance under laboratory conditions, especially MIL, ZIF, UiO and other series of MOFs, which are widely used in the field of gas separation due to their high selectivity and thermal stability for CO2. However, despite the huge potential of MOF materials in carbon capture, the prior art still has many limitations in practical applications. First, the structure of MOF materials may degrade under high humidity and high temperature conditions, especially in humid environments, some MOFs will undergo hydrolysis reactions, resulting in a significant decrease in adsorption performance. Secondly, the adsorption capacity and selectivity of MOF for CO2 may not be ideal under different operating conditions, especially under high pressure or high temperature conditions, the performance degradation is more obvious. In addition, the preparation cost of MOF is high and the process is complicated, which makes its large-scale industrial application face challenges. Furthermore, the recyclability and regeneration performance issues of MOF materials also limit their widespread application in carbon capture. Some materials require high-temperature or high-energy regeneration methods after adsorbing CO2, which increases operating costs. Summary of the invention
[0005] In view of this, the main purpose of the present invention is to provide a MOF glass fiber composite material and its preparation method and application. The problem to be solved is to composite MOF with glass fiber and perform functional treatment to make it have efficient CO2 adsorption performance and gas selectivity, achieve low-energy regeneration, enhance the mechanical strength and thermal stability of the material, and make it suitable for industrial environments.
[0006] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. The present invention proposes a MOF glass fiber composite material, comprising:
[0007] Fiberglass substrate;
[0008] MOF material, which is supported on the surface of the glass fiber substrate;
[0009] The functional modification layer is located on the surface of the MOF material; the functional modification layer contains one of an amino group, a carboxyl group and a hydroxyl group.
[0010] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0011] Preferably, in the aforementioned MOF glass fiber composite material, the glass fiber substrate is selected from one of S-glass fiber, alkali-free glass fiber, Vetrotex glass fiber and silica glass fiber.
[0012] Preferably, in the aforementioned MOF glass fiber composite material, the MOF material is selected from one of UiO-66, MIL-101 and MOF-808.
[0013] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. A method for preparing a MOF glass fiber composite material proposed in the present invention comprises the following steps:
[0014] S1: cleaning and pre-treating the surface of the glass fiber substrate;
[0015] S2 depositing MOF material on the surface of the glass fiber substrate obtained in step S1 to obtain a crude MOF glass fiber composite material;
[0016] S3 functionalizes the crude MOF glass fiber composite material obtained in step S2 to obtain a functional MOF glass fiber composite material;
[0017] S4: drying and activating the functionalized MOF glass fiber composite material obtained in step S3 to obtain the MOF glass fiber composite material.
[0018] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0019] Preferably, the preparation method of the aforementioned MOF glass fiber composite material, wherein the preparation method comprises the following steps:
[0020] S1 Glass fiber pretreatment: Clean and dry the glass fiber substrate to remove surface impurities;
[0021] S2 MOF synthesis and loading: The glass fiber substrate is immersed in the MOF precursor solution, and the MOF material is deposited and grown on the surface of the glass fiber by controlling the temperature and reaction time;
[0022] S3 functionalization treatment: performing subsequent surface functionalization treatment on the glass fiber material loaded with MOF;
[0023] S4 drying and activation: vacuum drying the functionalized composite material to obtain the MOF glass fiber composite material.
[0024] Preferably, the preparation method of the aforementioned MOF glass fiber composite material, wherein step S1 specifically comprises: placing the glass fiber in an atmosphere of nitrogen or argon with a purity of more than 99.99%, heating at 300-400°C for 30-60 min, then centrifugally washing the glass fiber with deionized water at 2000-3000 rpm / min for 3-5 min, repeating 3-4 times; and then drying at 60-80°C for 6-12 h.
[0025] Preferably, in the aforementioned method for preparing the MOF glass fiber composite material, in step S2, the MOF precursor solution comprises a metal salt and an organic ligand; the metal salt is zinc nitrate, cobalt nitrate or copper nitrate; and the organic ligand is terephthalic acid, imidazole or 2,5-dihydroxyterephthalic acid.
[0026] Preferably, in the aforementioned method for preparing the MOF glass fiber composite material, in step S2, the deposition thickness of the MOF material on the surface of the glass fiber is 1-5 μm.
[0027] Preferably, in the aforementioned method for preparing the MOF glass fiber composite material, in step S3, the subsequent surface functionalization treatment is to modify the MOF structure using an amination agent, a carboxylation agent or a hydroxylation agent.
[0028] Preferably, in the aforementioned method for preparing the MOF glass fiber composite material, in step S3, the amination agent is 3-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane or ethylenediamine.
[0029] Preferably, in the aforementioned method for preparing the MOF glass fiber composite material, in step S3, the carboxylation agent is 4-oxybenzoic acid or succinic anhydride.
[0030] Preferably, in the aforementioned method for preparing the MOF glass fiber composite material, in step S3, the hydroxylation agent is ethylene glycol or propylene glycol.
[0031] Preferably, in the aforementioned method for preparing the MOF glass fiber composite material, in step S4, the vacuum drying temperature is 50-80° C., the vacuum degree is 50-200 Pa, and the time is 4-24 hours.
[0032] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. The present invention proposes an application of a MOF glass fiber composite material in industrial capture of carbon dioxide emission reduction, wherein the MOF glass fiber composite material comprises:
[0033] Fiberglass substrate;
[0034] MOF material, which is supported on the surface of the glass fiber substrate;
[0035] The functional modification layer is located on the surface of the MOF material; the functional modification layer contains one of an amino group, a carboxyl group and a hydroxyl group.
[0036] By means of the above technical solution, the MOF glass fiber composite material provided by the present invention and its preparation method and application have at least the following advantages:
[0037] 1. Improve CO2 capture efficiency: By loading MOF on glass fiber composite materials, the high specific surface area and adjustable pore structure of MOF are used to significantly improve the CO2 capture efficiency; the design of the MOF glass fiber composite material effectively improves the adsorption capacity and adsorption rate, which is suitable for large-scale industrial emission scenarios and can more efficiently separate and capture CO2.
[0038] 2. Enhanced material mechanical strength and stability: The introduction of glass fiber enhances the mechanical strength and thermal stability of the composite material, enabling it to be used for a long time in high temperature and corrosive environments; compared with the use of MOF alone, the MOF glass fiber composite material has better durability, reduces material breakage and replacement frequency, and improves the service life and operational reliability of the equipment.
[0039] 3. Reduce costs and help reduce emissions: The combined design of the MOF glass fiber composite material can reduce the cost of carbon capture materials. At the same time, the composite of MOF and glass fiber has the advantages of being green, environmentally friendly and pollution-free. The material can be reused, which helps to reduce material consumption and replacement frequency. Compared with traditional adsorption materials, the MOF glass fiber composite material of the present invention is suitable for CO2 capture applications of different scales.
[0040] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION
[0041] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a MOF glass fiber composite material and its preparation method and application according to the present invention, its specific implementation, structure, characteristics and effects in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0042] The following materials or reagents, unless otherwise specified, were commercially available.
[0043] Some embodiments of the present invention provide a MOF glass fiber composite material, comprising:
[0044] Glass fiber substrate; the glass fiber substrate may be high-strength glass fiber, which can provide mechanical support and heat resistance to ensure that the material remains stable in high-temperature industrial environments. The optional glass fiber substrate may be alkali-free glass fiber (excellent electrical insulation, chemical resistance and corrosion resistance, low cost), high-strength glass fiber such as S-glass fiber and Vetrotex glass fiber (high tensile strength, impact resistance and high temperature resistance, enhanced structural strength), and high-temperature resistant glass fiber such as silica glass fiber (suitable for extreme high temperature applications, high temperature filtration and catalysis).
[0045] MOF material is loaded on the surface of a glass fiber substrate; the selection of the MOF material is based on its gas adsorption capacity, preferably a MOF with a large pore structure and a high surface area, such as UiO-66, MIL-101 or MOF-808. MOF glass fiber composite materials can achieve excellent gas adsorption performance by loading MOF with high specific surface area and large pores on a glass fiber substrate. Considering the thermal stability, chemical stability, substrate binding force and synthesis cost of MOF, it is ensured to be stable and durable in high temperature and humid environments.
[0046] Functionalized modification layer, which is located on the surface of MOF material; wherein the functionalized modification layer contains amino, carboxyl or hydroxyl groups, etc. Amino groups are basic groups that can interact with acidic molecules or gases (such as carbon dioxide), improve the selective adsorption of materials, and provide sites for further chemical modification; carboxyl groups enhance the binding with metal ions and polar molecules through hydrogen bonds and charge effects, and have excellent complexation and ion exchange capabilities; hydroxyl groups can increase the interaction with water and other polar molecules and improve hydrophilicity. The introduction of these polar groups can improve the hydrophilicity, reactivity and molecular capture efficiency of composite materials, and broaden their performance and application potential in applications such as water purification, gas capture, heavy metal removal and catalysis. Amino groups (-NH2), carboxyl groups, hydroxyl groups or other polar groups are introduced through surface functionalization treatment to enhance the adsorption performance of carbon dioxide.
[0047] Some embodiments of the present invention also provide a method for preparing a MOF glass fiber composite material, comprising the following steps:
[0048] S1: cleaning and pre-treating the surface of the glass fiber substrate;
[0049] S2 deposits MOF material on the surface of the glass fiber substrate;
[0050] S3 functionalized MOF glass fiber composites;
[0051] S4 performs drying and activation treatment.
[0052] In the above technical scheme, the present invention loads the MOF material on the surface of the glass fiber by a solution method; uses solvent evaporation technology or chemical vapor deposition (CVD) to further optimize the uniform attachment of MOF; introduces functional molecules (such as amino groups, carboxyl groups, etc.) into the MOF structure or the glass fiber surface to enhance the interaction between CO2 molecules and the material.
[0053] In specific implementation, the preparation method may include the following steps:
[0054] (1) Glass fiber pretreatment: The glass fiber substrate is cleaned and dried to remove surface impurities and ensure that the MOF can be evenly attached. Specifically, the glass fiber is placed in an atmosphere of nitrogen or argon with a purity of more than 99.99%, and heated at 300-400°C for 30-60 minutes to remove the sizing agent and possible organic matter on the fiber surface; then the glass fiber is centrifuged and washed with deionized water at 2000-3000rpm / min for 3-5 minutes, and repeated 3-4 times; then dried at 60-80°C for 6-12 hours; if the temperature is lower than 300°C, the cleaning is not thorough, and if the temperature is higher than 400°C, the fiber surface is damaged; if the insulation time is less than 30 minutes, the cleaning is not thorough; if the insulation time is greater than 60 minutes, the fiber surface is over-soaked and the surface is damaged. If the speed is less than 2000rpm / min, the speed is low, the time cost increases, and the centrifugation is incomplete; if the speed is greater than 3000rpm / min, the speed is too fast and exceeds the machine's use range; if the centrifugation time is less than 3min, the time is too short and the cleaning is incomplete; if the centrifugation time is greater than 5min, the time is too long and the time cost increases.
[0055] (2) MOF synthesis and loading: The glass fiber substrate is immersed in the MOF precursor solution. By controlling the temperature and reaction time, the MOF material is gradually deposited and grown on the surface of the glass fiber. The MOF precursor solution includes a metal salt and an organic ligand; the metal salt can be zinc nitrate, cobalt nitrate or copper nitrate, etc., which is used to provide a metal source in MOF synthesis; the organic ligand can be terephthalic acid (for UiO and MIL), imidazole (for ZIF) or 2,5-dihydroxyterephthalic acid (for MOF-74 series), etc. For example, for UiO, the molar ratio of the metal precursor (such as Zr salt) to terephthalic acid is 1:1-1:2; UiO helps to improve the yield when the ligand is excessive, but too much ligand may lead to structural defects or the formation of secondary structures. For the MIL type, the molar ratio of the metal precursor (such as Cr or Fe salt) to terephthalic acid is 1:1 or 1:1.5; for the MOF series, the molar ratio of the metal precursor to 2,5-dihydroxyterephthalic acid is 1:1. The temperature and reaction time are closely related to the type of load. The deposition thickness of the MOF material on the surface of the glass fiber is 1-5μm. When it is less than 1μm, it is not fully covered, and when it is higher than 5μm, it is easy to agglomerate and fall off.
[0056] (3) Functionalization treatment: The glass fiber material loaded with MOF is subjected to subsequent surface functionalization treatment, such as using an amination agent, a carboxylation agent or a hydroxylation agent to modify the MOF structure, thereby enhancing its affinity for CO2. The amination agent can be 3-aminopropyltriethoxysilane (APTES), N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (AEAPS) or ethylenediamine (EDA); the carboxylation agent is 4-oxybenzoic acid or succinic anhydride; the hydroxylation agent is ethylene glycol or propylene glycol; the amino group is a basic group that can interact with acidic molecules or gases (such as carbon dioxide) to enhance the selective adsorption of the material and provide sites for further chemical modification. The carboxyl group can effectively form a strong interaction force with the MOF material through electrostatic or hydrogen bonding, thereby improving the dispersibility of MOF in the glass fiber matrix; the hydroxyl group can also improve the dispersibility of MOF in the glass fiber and increase the structural uniformity of the composite material through hydrogen bonding and electrostatic effects.
[0057] (4) Drying and activation: The functionalized composite material is vacuum dried at 50-80°C and 50-200 Pa for 4-24 h to remove the residues in the pores and ensure the adsorption performance of the material.
[0058] The reason for choosing vacuum drying is mainly because: 1. Preventing damage to the MOF structure: Under vacuum conditions, water or solvents can evaporate at a lower temperature, reducing the damage to the MOF structure caused by thermal stress and protecting its large pore structure and high specific surface area; 2. Improving drying efficiency: Vacuum drying can remove moisture more quickly and thoroughly, reduce drying time, and avoid residual moisture affecting the adsorption capacity of the material; 3. Maintaining the integrity of active sites: Vacuum drying can avoid thermal decomposition, protect the active sites of MOF, and ensure the stability and adsorption performance of the composite material in subsequent applications.
[0059] The selection of 50-200Pa is to ensure a low residual gas pressure, quickly remove water or solvent, and prevent the collapse of the material structure. Considering the thermal stability of MOF, 50-80℃ is selected. According to the thickness of the material and the amount of solvent, the time is controlled between 4-24 hours to ensure that the water evaporates completely. Below 50℃ or less than 4h, the time cost increases and the drying is not thorough. Above 80℃ or more than 24h may damage the internal structure of MOF, resulting in a decrease in adsorption performance.
[0060] Some embodiments of the present invention further provide an application of a MOF glass fiber composite material in industrial capture of carbon dioxide emission reduction; the MOF glass fiber composite material comprises:
[0061] Fiberglass substrate;
[0062] MOF material, which is supported on the surface of the glass fiber substrate;
[0063] The functional modification layer is located on the surface of the MOF material; the functional modification layer contains one of an amino group, a carboxyl group and a hydroxyl group.
[0064] The CO2 adsorption performance of the MOF glass fiber composite material is tested using a gas adsorption tester, and the specific steps include:
[0065] (1) Adsorption reaction
[0066] The MOF / glass fiber composite material was placed in a column adsorption reactor, and a gas mixture containing CO2 (CO2: N2 = 2: 8 (v / v)) was introduced into the reactor. The gas pressure and temperature in the reactor were controlled (40°C / 10min). Within the set adsorption time of 60min, the gas flow rate was kept constant at 75mL / min to ensure that the CO2 molecules could fully enter the pores of the MOF / glass fiber composite material and adsorb to its active sites. At the same time, the time (breakthrough time) and flow rate of the gas passing through the column were recorded. According to the breakthrough curve, the adsorption capacity of CO2 was calculated.
[0067] (2) Adsorption saturation detection
[0068] By online detection of the volume percentage concentration of CO2 at the gas outlet, it is determined whether the adsorption of the MOF / glass fiber composite material has reached saturation. When the concentration of CO2 in the outlet gas tends to be stable, it indicates that the adsorption capacity of the MOF / glass fiber material is close to saturation.
[0069] The specific implementation methods of the present invention are further described in detail below in conjunction with the embodiments, but it should not be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0070] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.
[0071] The tensile strengths in Examples 1-5 and Comparative Example 1 were tested using a universal material testing machine in accordance with ASTM D2343 or ISO 527 standards.
[0072] Example 1: Preparation of UiO-66(Zr) / glass fiber composite material
[0073] 1. Material preparation: The cleaned alkali-free glass fiber sample (10 g, length 10 cm, diameter 10-20 μm) was immersed in a MOF precursor solution prepared by 1.0 mol / L ZrCl4 and terephthalic acid (1.0 mol / L). The reaction temperature was controlled at 120 ° C and the reaction time was 24 h. The UiO-66 (Zr) composite material was obtained by solvent self-assembly of MOF material.
[0074] 2. Surface functionalization: The obtained UiO-66 (Zr) composite material was immersed in a 2.5 wt % ethylenediamine solution at room temperature for 12 h to introduce amino functional groups on the surface of UiO-66 to obtain a composite material.
[0075] 3. Activation drying process: The obtained composite material is vacuum dried at 120° C. for 8 h to obtain the UiO-66(Zr) / glass fiber composite material.
[0076] Performance test: At standard temperature (25°C) and standard atmospheric pressure, the UiO-66 (Zr) / glass fiber composite material obtained above was subjected to an adsorption test using CO2 gas. The results showed that the adsorption capacity of the UiO-66 (Zr) / glass fiber composite material for CO2 was 2.19 mmol / g; in addition, the tensile strength of the composite material (2491.5 MPa) was increased by 29.7% compared to the tensile strength of pure glass fiber (1921 MPa).
[0077] Comparative Example 1: Preparation of UiO-66(Zr) / glass fiber composite material
[0078] 1. Material preparation: The cleaned alkali-free glass fiber sample (10 g, length 10 cm, diameter 10-20 μm) was immersed in a MOF precursor solution prepared by 1.0 mol / L ZrCl4 and terephthalic acid (1.0 mol / L). The reaction temperature was controlled at 120 ° C and the reaction time was 24 h. The UiO-66 (Zr) composite material was obtained by solvent self-assembly of MOF material.
[0079] 2. Activation drying process: The obtained UiO-66(Zr) composite material was vacuum dried at 120°C for 8 h to obtain an unfunctionalized UiO-66(Zr) / glass fiber composite material.
[0080] Performance test: At standard temperature (25°C) and standard atmospheric pressure, the unfunctionalized UiO-66 (Zr) / glass fiber composite material obtained above was subjected to an adsorption test using CO2 gas. The results showed that the adsorption capacity of CO2 by the unfunctionalized UiO-66 / glass fiber composite material was 1.24 mmol / g, which was much lower than the adsorption capacity of CO2 by the UiO-66 (Zr) / glass fiber composite material in Example 1 (2.19 mmol / g). In addition, the tensile strength (2205.3 MPa) of the unfunctionalized UiO-66 / glass fiber composite material was increased by 14.5% compared to the tensile strength (1921 MPa) of pure alkali-free glass fiber.
[0081] Example 2: Preparation of MIL-101(Cr) / glass fiber composite material
[0082] 1. Material preparation: Take 1.35g of terephthalic acid (DBC) and add it to about 30g of water, stir at room temperature for 30min to obtain a suspension containing DBC; Take 3.3g of Cr(NO3)3·9H2O and completely dissolve it in 30g of water, pour it into the suspension containing DBC, add 1.1mL of 40wt% hydrofluoric acid solution, continue stirring for 60min, transfer it to a reactor, immerse the alkali-free glass fiber sample (10g, length 10cm, diameter 10-20μm) in it and heat it to 220℃, stir and react for 12h. After the reaction is completed, cool it to room temperature, then centrifuge and wash it 5 times at a speed of 3000rpm / min, 5min, and then place it in an oven at 80℃ for 12h to obtain a MIL-101(Cr) composite material.
[0083] 2. Surface modification: The obtained MIL-101(Cr) composite material was immersed in a 5 wt % chloroacetic acid (ClCH2COOH) solution at 60° C. for 12 h (stirring speed was 250 rpm) to obtain a composite material.
[0084] 3. Drying treatment: The obtained composite material was vacuum dried at 120° C. for 8 h to obtain the MIL-101(Cr) / glass fiber composite material.
[0085] Performance test: At standard temperature (25°C) and standard atmospheric pressure, the MIL-101(Cr) / glass fiber composite material obtained above was subjected to an adsorption test using CO2 gas. The results showed that the CO2 adsorption capacity of the MIL-101(Cr) / glass fiber composite material obtained above reached 1.95mmol / g at standard atmospheric pressure, showing a strong gas capture ability; in addition, the tensile strength (2537.6MPa) of the MIL-101(Cr) / glass fiber composite material was increased by 32.1% compared to the tensile strength (1921MPa) of pure alkali-free glass fiber.
[0086] Example 3: Preparation of TEPA@MOF-808 glass fiber composite material
[0087] 1. Material preparation: 3.1 mmol of H3BTC (1,3,5-benzenetricarboxylic acid) and zirconium oxychloride octahydrate ZrOCl2·8H2O (1.012 g, 3.1 mmol) were added to a DMF / HCOOH mixture (DMF = N,N-dimethylformamide, 54 mL / 72 mL) in a 250 mL screw-cap conical flask containing 1 g of an alkali-free glass fiber sample (length 10 cm, diameter 10-20 μm). The resulting mixture was treated with ultrasound (power 100 W) for 10 min until a clear solution was obtained, and then the clear solution was heated in a constant temperature oven at 135 ° C for 48 h to obtain a MOF-808 / glass fiber composite material.
[0088] 2. Surface modification: The obtained MOF-808 / glass fiber composite material was added to 5% (w / v) tetraethylenepentamine (TEPA) methanol and stirred at 40°C for 6 h to evaporate completely to obtain a light yellow fiber solid (i.e., unwashed MOF-808 / glass fiber composite material).
[0089] 3. Drying treatment: The obtained composite material is washed with anhydrous ethanol, and then allowed to stand for stratification; and dried in a drying oven at 80° C. for 12 hours to obtain the TEPA@MOF-808 glass fiber composite material.
[0090] Performance test: At standard temperature (25°C) and standard atmospheric pressure, the TEPA@MOF-808 glass fiber composite material was subjected to an adsorption test using CO2 gas. The results showed that the adsorption capacity of TEPA@MOF-808 for CO2 was 2.58mmol / g; in addition, the tensile strength (2399.3MPa) of the TEPA@MOF-808 glass fiber composite material was increased by 24.9% compared to the tensile strength (1921MPa) of pure alkali-free glass fiber.
[0091] Example 4: Preparation of MIL-101(Cr) / glass fiber composite material
[0092] 1. Material preparation: Take 1.35g of terephthalic acid (DBC) and add it to about 30g of water, stir at room temperature for 30min to obtain a suspension containing DBC; Take 3.3g of Cr(NO3)3·9H2O and completely dissolve it in 30g of water, pour it into the suspension containing DBC, add 1.1mL of 40wt% hydrofluoric acid solution, continue stirring for 60min, transfer it to a reactor, immerse the S-glass fiber sample (10g, length 10cm, diameter 10-20μm) in it and heat it to 220℃, stir and react for 12h. After the reaction is completed, cool it to room temperature, then centrifuge and wash it 5 times at a speed of 3000rpm / min, 5min, and then place it in an oven at 80℃ for 12h to obtain a MIL-101(Cr) composite material.
[0093] 2. Surface modification: The obtained MIL-101(Cr) composite material was immersed in a 2.5 wt % ethylenediamine solution at room temperature for 12 h to obtain a composite material.
[0094] 3. Drying treatment: The obtained composite material was vacuum dried at 120° C. for 8 h to obtain the MIL-101(Cr) / glass fiber composite material.
[0095] Performance test: At standard temperature (25°C) and standard atmospheric pressure, the MIL-101(Cr) / glass fiber composite material obtained above was subjected to an adsorption test using CO2 gas. The results showed that the CO2 adsorption capacity of the MIL-101(Cr) / glass fiber composite material obtained above reached 2.03mmol / g at standard atmospheric pressure, showing a strong gas capture ability; in addition, the tensile strength (5828MPa) of the MIL-101(Cr) / glass fiber composite material was increased by 27.2% compared to the tensile strength (4582MPa) of pure S-glass fiber.
[0096] Example 5: Preparation of MOF-808 glass fiber composite material
[0097] 1. Material preparation: 3.1 mmol of H3BTC (1,3,5-benzenetricarboxylic acid) and zirconium oxychloride octahydrate ZrOCl2·8H2O (1.012 g, 3.1 mmol) were added to a DMF / HCOOH mixture (DMF = N,N-dimethylformamide, 54 mL / 72 mL) in a 250 mL screw-cap conical flask containing 1 g of S-glass fiber sample (length 10 cm, diameter 10-20 μm), and the resulting mixture was treated with ultrasound (power 100 W) for 10 min until a clear solution was obtained, and then the clear solution was heated in a constant temperature oven at 135 ° C for 48 h to obtain a MOF-808 / glass fiber composite material.
[0098] 2. Surface modification: The obtained MOF-808 / glass fiber composite material was immersed in 5 wt % chloroacetic acid (ClCH2COOH) at 60° C. for 12 h (stirring speed was 250 rpm) to obtain a composite material.
[0099] 3. Drying treatment: The obtained composite material is washed with anhydrous ethanol, and then allowed to stand for stratification; and dried in a drying oven at 80° C. for 12 hours to obtain the MOF-808 glass fiber composite material.
[0100] Performance test: At standard temperature (25°C) and standard atmospheric pressure, the MOF-808 glass fiber composite material was subjected to an adsorption test using CO2 gas. The results showed that the adsorption capacity of the MOF-808 glass fiber composite material for CO2 was 2.24mmol / g; in addition, the tensile strength (5837MPa) of the MOF-808 glass fiber composite material was increased by 27.4% compared to the tensile strength (4582MPa) of pure S-glass fiber.
[0101] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0102] The numerical range described in the present invention includes all the numerical values within the range, and includes the range value formed by any two numerical values within the range. Different numerical values of the same indicator appearing in all embodiments of the present invention can be arbitrarily combined to form a range value.
[0103] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.
[0104] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A MOF glass fiber composite material, characterized in that: Include: Fiberglass substrate; MOF material, which is supported on the surface of the glass fiber substrate; The functional modification layer is located on the surface of the MOF material; the functional modification layer contains one of an amino group, a carboxyl group and a hydroxyl group.
2. The MOF glass fiber composite material according to claim 1, characterized in that: The glass fiber substrate is selected from one of S-glass fiber, alkali-free glass fiber, Vetrotex glass fiber and silica glass fiber; the MOF material is selected from one of UiO-66, MIL-101 and MOF-808.
3. A method for preparing a MOF glass fiber composite material, characterized in that: The following steps are involved: S1: cleaning and pre-treating the surface of the glass fiber substrate; S2 depositing MOF material on the surface of the glass fiber substrate obtained in step S1 to obtain a crude MOF glass fiber composite material; S3 functionalizes the crude MOF glass fiber composite material obtained in step S2 to obtain a functional MOF glass fiber composite material; S4: drying and activating the functionalized MOF glass fiber composite material obtained in step S3 to obtain the MOF glass fiber composite material.
4. The preparation method according to claim 3, characterized in that: The preparation method comprises the following steps: S1 Glass fiber pretreatment: Clean and dry the glass fiber substrate to remove surface impurities; S2 MOF synthesis and loading: The glass fiber substrate is immersed in the MOF precursor solution, and the MOF material is deposited and grown on the surface of the glass fiber by controlling the temperature and reaction time; S3 functionalization treatment: performing subsequent surface functionalization treatment on the glass fiber material loaded with MOF; S4 Drying and Activation: The functionalized composite material is vacuum dried to obtain the MOF glass fiber composite material.
5. The preparation method according to claim 4, characterized in that: Step S1 specifically includes: placing the glass fiber in an atmosphere of nitrogen or argon with a purity of more than 99.99%, heating at 300-400°C for 30-60 minutes, then centrifugally washing the glass fiber with deionized water at 2000-3000rpm / min for 3-5 minutes, repeating 3-4 times; and then drying at 60-80°C for 6-12 hours.
6. The preparation method according to claim 4, characterized in that: In step S2, the MOF precursor solution includes a metal salt and an organic ligand; the metal salt is zinc nitrate, cobalt nitrate or copper nitrate; the organic ligand is terephthalic acid, imidazole or 2,5-dihydroxyterephthalic acid; and the deposition thickness of the MOF material on the surface of the glass fiber is 1-5 μm.
7. The preparation method according to claim 4, characterized in that: In step S3, the subsequent surface functionalization treatment is to modify the MOF structure using an amination agent, a carboxylation agent or a hydroxylation agent.
8. The preparation method according to claim 7, characterized in that: In step S3, the amination reagent is 3-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane or ethylenediamine; the carboxylation reagent is 4-oxybenzoic acid or succinic anhydride; and the hydroxylation reagent is ethylene glycol or propylene glycol.
9. The preparation method according to claim 4, characterized in that: In step S4, the vacuum drying temperature is 50-80°C, the vacuum degree is 50-200Pa, and the time is 4-24h.
10. Application of MOF glass fiber composite material in industrial capture of carbon dioxide emission reduction, characterized in that: The MOF glass fiber composite material comprises: Fiberglass substrate; MOF material, which is supported on the surface of the glass fiber substrate; The functional modification layer is located on the surface of the MOF material; the functional modification layer contains one of an amino group, a carboxyl group and a hydroxyl group.
Citation Information
Patent Citations
Preparation method for amino modified adsorption material
CN103721679A
MOFs based carbon dioxide adsorbent, preparation method and application thereof
CN104056598A
UIO-66-X-loaded glass fiber compound as well as preparation method and application thereof
CN113769714A
Polymer composite solid electrolyte, preparation method and application thereof
CN118136938A
MOF (Metal Organic Framework) material based on glass fiber load, preparation method and air water collection device
CN118831577A